Happiness burnout and coping styles in a private company - L. Arias, Walter (2014)
In this paper the relationship between happiness, burnout and coping styles in 74 workers (44 men and 30 women) from a private company Arequipa are analyzed. This Happiness Scale Lima was used, the Maslach Burnout Inventory and Coping Behaviors Questionnaire in situations of stress. The results suggest that there are significant relationships (p <0.001, p <0.005) between burnout and happiness, and burnout and coping, but not between happiness and coping styles. Moreover, in older men’s lower levels of emotional exhaustion and depersonalization. While the level of education was negatively associated in women with low personal accomplishment. Coping styles are distinctive from each genre: while men prefer active coping style in women predominate and passive avoidant styles, so that among women there is a negative relationship (r = -, 372) between joy live and active coping style, and among men, the passive style is positively related to depersonalization and burnout.